2002
DOI: 10.1055/s-2002-19322
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Preparation of 2-(Hydroxymethyl)vinylphosphonates by Insertion of Ketones into Zirconacycle Phosphonates

Abstract: Three-member zirconacycles insert ketones exclusively at C-2 to give five-member zirconacycle phosphonates that can be hydrolyzed to give 2-(hydroxymethyl)vinylphosphonates, 2, in excellent yields. Other regioisomers were not detected. The reaction works well for both aromatic and aliphatic ketones. Competitive studies indicate that ketones and aldehydes insert at about the same rate and that both react much faster than alkynes. Compounds 2 undergo chlorination with thionyl chloride without rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The free phosphonic acid compounds 5Ϫ7 were obtained by the hydrolysis of the phosphonate esters by Me 3 SiBr in CH 2 Cl 2 . The other types of 2-(hydroxymethyl)vinylphosphonic acids 8Ϫ14 were obtained by insertion of aldehydes or ketones into the zirconacycle (Scheme 1) and, similarly, were hydrolyzed [28,29]. The 3-oxovinylphosphonic acids 15Ϫ18 were prepared by insertion of acid chlorides into zirconacycles (Scheme 1), followed by similar hydrolysis with Me 3 SiBr [30].…”
Section: Methodsmentioning
confidence: 99%
“…The free phosphonic acid compounds 5Ϫ7 were obtained by the hydrolysis of the phosphonate esters by Me 3 SiBr in CH 2 Cl 2 . The other types of 2-(hydroxymethyl)vinylphosphonic acids 8Ϫ14 were obtained by insertion of aldehydes or ketones into the zirconacycle (Scheme 1) and, similarly, were hydrolyzed [28,29]. The 3-oxovinylphosphonic acids 15Ϫ18 were prepared by insertion of acid chlorides into zirconacycles (Scheme 1), followed by similar hydrolysis with Me 3 SiBr [30].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, insertion of ketones into the phosphonate zirconacycles proceeds both with complete stereoand regiospecificity, into C2 of the zirconacycle to provide after hydrolysis 2-(hydroxymethyl)vinylphosphonates, 10 (Scheme 2) [26].…”
Section: Reactions Of 1-alkenylphosphonates Zirconium Complexes With mentioning
confidence: 99%
“…A possible mechanism involves attack by the Grignard on an intermediate cyclopropene oxide. The sequence is equivalent to syn addition of a Grignard followed by an aldehyde [23,26,27].…”
Section: Synthesis Of Various Di-and Tri-substituted Vinylphosphonatesmentioning
confidence: 99%
“…[1][2][3] Phosphonates and aminophosphonates have been found to possess chelating properties toward metals, 4 irreversible inhibition properties against serine proteases 5 and the ability to inhibit zinc-dependent enzymes of the metalloprotease family. [6][7][8] As part of ongoing research in our laboratory, we have reported different synthetic methods for the synthesis of novel, highly substituted vinyl phosphonate compounds from 1-alkynylphosphonates using zirconium(II) or titanium(II) reagents, [9][10][11][12][13][14][15][16][17][18][19][20] as well as the synthesis of fusedcyclopentenone phosphonates from 1-alkynylphosphonates via an intramolecular Pauson-Khand reaction 21 using molybdenum hexacarbonyl [Mo(CO) 6 ]. 22 In the course of our research on fused-cyclopentenone phosphonate compounds, 21 we encountered double bond migration.…”
mentioning
confidence: 99%